Biological control: supplement published - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
The Australian Centre for International Agricultural Research (ACIAR) has published the first supplement to Biological control: Pacific prospects, by D F Waterhouse and K R Norris, which was published in 1987. The supplement covers six further...